Inside out : a memoir - Moore, Demi (Harper, an imprint of HarperCollinsPublishers, 2019)
"Even as Demi was becoming the highest paid actress in Hollywood, however, she was always outrunning her past, just one step ahead of the doubts and insecurities that defined her childhood. Throughout her rise to fame and during some of the most pivotal moments of her life, Demi battled addiction, body image issues, and childhood trauma that would follow her for years all while juggling a skyrocketing career and at times negative public perception. As her success grew, Demi found herself questioning if she belonged in Hollywood, if she was a good mother, a good actress and, always, if she was simply good enough."--